Supplier-dependent differences in intermittent voluntary alcohol intake and response to naltrexone in Wistar rats - Momeni, Shima; Segerström, Lova; Roman, Erika (Frontiers in Neuroscience, 2015)
Alcohol use disorder (AUD) is a worldwide public health problem and a polygenetic disorder displaying substantial individual variation. This work aimed to study individual differences in behavior and its association to voluntary alcohol intake and subsequent response to naltrexone in a seamless heterogenic group of animals. Thus, by this approach the aim was to more accurately recapitulate the existing heterogeneity within the human population. Male Wistar rats from three different suppliers (Harlan Laboratories B.V., RccHanTM:WI; Taconic Farms A/S, HanTac:WH; and Charles River GmbH, Crl:WI )were used to create a heterogenic group for studies of individual differences in behavior, associations to intermittent voluntary alcohol intake and subsequent response to naltrexone. The rats were tested in the open field prior to the Y-maze and then given voluntary intermittent access to alcohol or water in the home cage for six weeks, where after, naltrexone in three different doses or saline was administered in a Latin square design over four weeks and alcohol intake and preference was measured. However, supplier-dependent differences and concomitant skew subgroup formations, primarily in open field behavior and intermittent alcohol intake, resulted in a shifted focus to instead study voluntary alcohol intake and preference, and the ensuing response to naltrexone in Wistar rats from three different suppliers. The results showed that outbred Wistar rats are diverse with regard to voluntary alcohol intake and preference in a supplier-dependent manner; higher in RccHanTM:WI relative to HanTac:WH and Crl:WI. The results also revealed supplier-dependent differences in the effect of naltrexone that were dose- and time-dependent; evident differences in high-drinking RccHanTM:WI rats relative to HanTac:WH and Crl:WI rats. Overall these findings render RccHanTM:WI rats more suitable for studies of individual differences in voluntary alcohol intake and response to naltrexone and further highlight the inherent heterogeneity of the Wistar strain. The overall results put focus on the importance of thoroughly considering the animals used to aid in study design and for comparison of reported results.